Curiosity Emerging From the Perception of Change in Music. (July 2022) - Omigie, Diana; Ricci, Jessica
Music offers a useful opportunity to consider the factors contributing to the experience of curiosity in the context of dynamically changing stimuli. Here, we tested the hypothesis that the perception of change in music triggers curiosity as to how the heard music will unfold. Participants were presented with unfamiliar musical excerpts and asked to provide continuous ratings of their subjective experience of curiosity and calm, and their perception of change, as the music unfolded. As hypothesized, we found that for all musical pieces, the perceptual experience of change Granger-caused feelings of curiosity but not feelings of calm. Our results suggest music is a powerful tool with which to examine the factors contributing to curiosity induction. Accordingly, we outline ways in which extensions to the approach taken here may be useful: both in elucidating our information-seeking drive more generally, and in elucidating the manifestation of this drive during music listening.